2017
DOI: 10.1177/1687814017728837
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model of plate rolling force with a simple available velocity field and equal perimeter yield criterion

Abstract: To analyze plate rolling force, a simple available velocity field is first proposed in this article. Based on the velocity field, the internal deformation energy rate and the friction energy rate are analyzed by the equal perimeter yield criterion and the method of the collinear vector inner product, respectively. Finally, the rolling force accounting for the elastic flattening of the roller and the temperature rise of the rolled piece are ultimately obtained through the minimization of the total energy rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Wang et al [13] suggested the mathematical expression of the equal perimeter EP yield criterion and the derivation of the specific plastic work rate. The mathematical expression of the EP yield criterion in the Haigh-Westergaard stress space: (6) The geometric representation of the yield criterion on the -plane is equilateral but nonequiangular as shown in Figure 5.…”
Section: The Power Of Deformationmentioning
confidence: 99%
“…Wang et al [13] suggested the mathematical expression of the equal perimeter EP yield criterion and the derivation of the specific plastic work rate. The mathematical expression of the EP yield criterion in the Haigh-Westergaard stress space: (6) The geometric representation of the yield criterion on the -plane is equilateral but nonequiangular as shown in Figure 5.…”
Section: The Power Of Deformationmentioning
confidence: 99%